Religious Moderation in the Discourse of Nahdlatul Ulama’s Dakwah in the Era of Industry 4.0 - Umi Musyarrofah; Zulhannan Zulhannan (Millah: Journal of Religious Studies, 2023)
This study analyzes religious moderation in the discourse of Nahdlatul Ulama’s dakwah in the era of Industry 4.0. The objective of this inquiry is to analyze the substance, identify, and explore the actualization of the religious moderation movement in Indonesia within the discourse of Nahdlatul Ulama’s dakwah. This research employs a qualitative descriptive approach using a narrative review method. Secondary data from various sources, such as books, journals, and the internet, concerning Nahdlatul Ulama’s dakwah discourse were utilized. The research findings indicate that the substance of the religious moderation movement in Indonesia within the discourse of Nahdlatul Ulama’s dakwah revolves around the undeniable presence of religious diversity. This diversity is an intrinsic aspect that cannot be eradicated. The emergence of the religious moderation movement in Indonesia within the discourse of Nahdlatul Ulama’s dakwah prominently represents a key aspect in the history of civilization and traditions across various global religions. The actualization of the religious movement in Indonesia within the discourse of Nahdlatul Ulama’s dakwah encompasses three substantial dimensions: moderate religious thought, moderation through movements, and moderation within religious traditions and practices.